Design to Build A Shallots Drying House with Fumigation in District Tanah Miring - Indah Widanarti; sunardi sunardi; Ni luh Sri Suryaningsih (Musamus AE Featuring Journal, 2018)
The purpose of this study was to make a simple shallots drying house design with fumigation so that dried shallots were obtained in accordance with the Standar Nasional Indonesia (SNI). The method used in this study is the temperature measurement in the smoke house. The benchmark in testing the smoking house is the temperature used in the room at the smoke house with the construction of a small scale permanent building. The temperature that shallots have to accept is 35-40oC. Temperature data obtained from measurements at 3 observation points in the smoke house for heat transfer analysis. The test results on the design of the smoke house with a shelf design located 2 meters from the ground floor showed that convection heat transfer in the fumigation chamber was stable so as to produce dry shallots with a weight loss of 30%.